FDI and labour market: Empirical evidence from the states that joined the European Union in 2004 - Laura Diaconu; Daniel Sterbuleac (CES Working Papers, 2017)
The purpose of our study is to analyse the impact of FDI on the labour markets of the states that joined the EU in 2004, before and after the EU accession and in the context of the global economic crisis. To achieve this objective, we have investigated the literature and carried out a pooled OLS regression estimation. The analysis shows that, until 2003, FDI neither enhanced the labour force participation rate, nor reduced the youth unemployment in the analysed states. After EU adhesion, FDI had only one significant positive effect, exerted on real labour productivity, and negative effects on employment and labour force participation rate. In the context of the crisis, FDI had beneficial effects on the unemployment, but to a lesser extent on the youth unemployment. FDI did not have any significant effect on annual net earnings in none of the three periods.
Keywords: E24; J24; O19; 330; foreign direct investment; labour market; employment; net income; labour productivity